Pengaruh Model Pembelajaran Index Card Match Terhadap Motivasi Belajar Siswa Mata Pelajaran Pendidikan Pancasila - Tyas, Chusnul Ramadhaning; Pratiwi, Emy Yunita Rahma (IJPSE Indonesian Journal of Primary Science Education, 2024)
Motivation to learn is an encouragement or invitation to do something that can foster a sense of enthusiasm in a person so that the learning process can be achieved better. This research was conducted at SDN Kwaron 02 Diwek Jombang, this research aims to find out whether there is an influence of the index card match learning model on student learning motivation in class II of SDN Kwaron 02. To solve the problems in this research the researcher used the index card match learning model. This research uses a quantitative research approach with the Pre-Experimental Designs quantitative research type using the experimental design research method used, namely pre-experimental design using the One Group Pretset-Posttest Design research design. The research was conducted at SDN Kwaron 02 Diwek Jombang. Researchers used a saturated sampling technique because the number of students was less than 30 for respondents in this study, namely 15 students. In this research, two meetings were conducted, at the first meeting the students were not given an application, then at the second meeting the students were given the application of the index card match learning model. The data collection instruments in this research used questionnaires, interviews, and the research documentation was analyzed using SPSS 25.0. From the research results, it was found that there was an influence of the index card machine learning model on learning motivation in class II students at SDN Kwaron 02, this was supported by an average result of 73.667 which was greater than the average pretest result of 60.667. There is an influence of the index card match learning model on student learning motivation. From the calculation results using SPSS 25.0, it shows that there is an influence of the index card match learning model on students' learning motivation in class II at SDN Kwaron 02. From the results of the calculations, the t count is 16.516, while for t table 2, 144787, it can be concluded that Ho is rejected and Ha accepted.